The wonder of birds eaudiobook What they tell us about ourselves, the world, and a better future. - Robbins, Jim (Tantor Media, 2017)
Birds, Jim Robbins posits, are our most vital connection to nature. They compel us to look to the skies, both literally and metaphorically; draw us out into nature to seek their beauty; and let us experience vicariously what it is like to be weightless. Birds have helped us in so many of our human endeavors: learning to fly, providing clothing and food, and helping us better understand the human brain and body. The Wonder of Birds illuminates qualities unique to birds that demonstrate just how invaluable they are to humankind—both ecologically and spiritually. The wings of turkey buzzards influenced the Wright brothers' flight design; the chickadee's song is considered by scientists to be the most sophisticated language in the animal world; and the quietly powerful presence of eagles in the disadvantaged neighborhood of Anacostia proved to be an effective method for rehabilitating the troubled young people placed in charge of their care. Exploring both cutting-edge scientific research and our oldest cultural beliefs, Robbins moves these astonishing creatures from the background of our lives to the foreground.